MINDFULNESS BONDING INTERVENTION BETWEEN MOTHER AND FETUS USING AUDIO TOWARDS PREGNANT WOMEN'S ANXIETY AHEAD OF LABOR - Herawati, Meirita; Desriya, Nia; Sri Rahayu, Ari Oktora (Siklus : Journal Research Midwifery Politeknik Tegal, 2025)
Childbirth is a long process, 13-14 hours for primigravida mothers and 6-7 hours for multigravida mothers. In this situation, there are many changes and may cause stress. Neglecting this condition can negatively affect both parties. Mindfulness can help with anxiety in this study. Focusing on the present moment, environment, and activities around you is known as mindfulness. This study aims to determine how effective the use of audio is to reduce anxiety in pregnant women before labor through the relationship of self-awareness between mother and fetus. This study uses a pre-experiment method before and after the experiment in a one-group design. With the total sampling technique, the study population consisted of 21 pregnant women. TM III was conducted in the working area of Rejosari Health Center in July 2024. The Pregnancy Anxiety Scale questionnaire and audio recording were used as media. The results of the two mean difference test analyses showed that the anxiety level of respondents before the self-awareness intervention was 26.76 and after the intervention was 22.38, with a p-value of 0.000. This means that mindfulness activities using audio helped lower the anxiety of pregnant women before giving birth.